Alojz Gradnik in Heinrich Mann - Toroš, Ana (Slavistična revija, 2011)
The article first outlines the reception of the German author Heinrich Mann in the Slovene lands in the fitst half of the 20th century, and in the proceeding focuses on the specific, productive, reception of the Slovene poet Alojz Gradnik that is evident in the relationship between the novel Zwischen den Rassen and the sonnet Vprašanje (Question).
Keywords: 20.st.; German-language literature; Gradnik, Alojz, 1882-1967; history of literature; literarna zgodovina; literarni vplivi; Mann, Heinrich, 1871-1950; nemška književnost; nemški pisatelji; Slovene literature; slovenska književnost; slovenski pesniki